(untitled) (Transport systems and technologies, 2018)
In the article the analysis of the opportunities and prospects of prestressed bearing structures in railway engineering, including the construction of freight cars. Systematized information on the use of prestressed structures in different engineering vehicles that are elected by the criterion of similarity to the basic block and a design of railway engineering objects. Theoretical and practical features modern designs prestressed structures, as well as specific issues of their use.